Annual report: Non-Formal Primary Education (under rural development programme), December-1987 - BRAC (© BRAC, 2016)
1. Introduction 2. Education of Girls 3. The initial objectives of NFPE pilot project 4. Special feature of NFPE programme 5. The specific objective of NFPE programme 6. Basic aspects of NFPE 7. Statistical summery of NFPE 8. Expansion and growth 9. Performance of NFPE in 1986 10. Performance of NFPE in 1987 11. Overall Performance of NFPE 12. Teachers recruitment and training 13. Supervision and evaluation 14. Community participation 15. Monthly teachers meeting 16. Appendix.